(3TQM EVGAI GdOLfI aj YbGFO Cgd GdSfIs - (3eMeO Hf GdeNJGQ Hf GdCYeT GdYdhjs; (3GdebQj , CMeO Hf eMeO Hf CMeO Hf jMji GdJdeSGfj, CHh GdYHGS,J (B1041 (3g` s ((3eMeO Hf SjOi CMeO s)
(3ChdgG (B:s
(3GdMeO ddg GdPi HaVdg CVGAI GdOLfI hHYO aGdESJYGfI HGdehdi GdcQje Ydi TQM EVGAI EVGAI GdOLfI hgj bUjOI ai NeSeGFI HjJ , JTJed Ydi aUhd ef bhGYO Yde GdJhMjO , hCUhd LeYJ ef Gdaf , ZQQ ahGFOg s
(3BNQgG (B:s
(3hdgPG bGd GdfHi Udi Gddg Ydjg hSde ef cGf BNQ cdGeg dG Edg EdG Gddg ONd GdLfI , hbGd (B: (3hef eGJ hgh jYde Cf dG Edg EdG Gddg ONd GdLfI hgGgfG fXe GdYbGFO GfJgi eHdZkG def OYGg eG GfJgi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3TQM GdefXheI ai Yde GdJhMjOs
(3fSNI bOjeI heUMMI s
(3cJHJ HYV YHGQJgG HGdMeQI s
(3ChQGbgG eJbUaI s
Keywords: (3GdJhMjO hGdedd hGdfMds